Table of contents (Journal of Irish Urban Studies, Vol.3 (No. 1), 2004) - (:unkn) unknown (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
Table of contents, Journal of Irish Urban Studies, Vol.3 (Issue 1), 2004
Keywords: Urban geography -- Ireland